High prevalence but low referral rate of adrenal incidentalomas in a Lebanese tertiary hospital - Jambart, Isabelle; Wakim, Anne-Marie; Cheaib, Nadine; Lahoud, Christelle; Mansour, Maryam; Issa, Carla Bou; Daoud, Charbel; Moussa, Lina Menassa; Gannagé-Yared, Marie-Hélène; El Ghorayeb, Nada (Frontiers in Endocrinology, 2025)
IntroductionAdrenal incidentalomas (AI) are being more frequently reported with the advent of medical imaging. Studies on their prevalence, characteristics and functional status are lacking in the Middle East.ObjectiveTo determine the prevalence of AI as well as their clinical and radiological characteristics and referral rates to endocrinologists for hormonal testing.MethodsWe prospectively evaluated unselected adult patients who underwent an abdominal computed tomography (CT) between November 2022 and June 2023 at a Lebanese tertiary teaching hospital. An experienced radiologist carefully reviewed 4,464 CT. Patients with known or suspected malignancy or adrenal disease were excluded. Main outcome measures included prevalence of AI and referral rates to endocrinologists during a one-year follow-up.Results3168 CT were retained for analysis, 222 had an AI, with an overall prevalence of 7%. There was no significant difference in prevalence according to gender (8% in women, 6% in men p = .06.). The prevalence increased with age from 0.9% in young adults (18–30 years) to 10.8% in patients older than 70. Mean age of patients with AI was 69 ± 14 years. 46% were males. Median size of AI was 1.7 cm (1.2-2.5). 45% had a density <10 Hounsfield Unit (HU) and 17% were bilateral. Patients with an AI were significantly older (p <.0001), had a higher Body mass index (BMI) (p = .0021), more hypertension (p = .023), dyslipidemia (p = .002), and cardiovascular diseases (CVD) (p = .0056). No difference according to sex was noted. The referral rate of AI to endocrinologists was only 5.4%.ConclusionThe prevalence of AI in Lebanon is comparable to the worldwide prevalence and is linked to age, BMI, hypertension, dyslipidemia and CVD but not to gender. Despite this high prevalence, the rate of referral for appropriate investigations is poor. Raising awareness among clinicians is therefore essential for a better evaluation of these patients.